Pengaruh Motivasi, Persepsi, dan Sikap Konsumen terhadap Keputusan Pembelian Laptop ASUS (Studi Mahasiswa Universitas Islam Negeri Jurai Siwo Lampung ) - Ardi Anto; Aulia Rahma Septianingsih; Chabi Baturohmah; Della Amalia; Fikri Rizki Utama (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the influence of motivation, perception, and consumer attitude on the purchasing decision of ASUS laptops among students of UIN Jusila. The method used in this research is a quantitative approach with a sample of 75 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed with SPSS through validity testing, reliability testing, classical assumption tests, multiple linear regression, t-test, F-test, and the coefficient of determination. The results indicate that motivation does not have a significant effect on purchasing decisions, whereas consumer perception and attitude have a positive and significant effect. Simultaneously, the three variables significantly influence purchasing decisions with a contribution of 83.4%. Consumer attitude and perception are identified as the most dominant factors influencing students’ decisions to purchase ASUS laptops